Influence of viscoelastic characteristics of the colloidal suspensions on the formation of SnO2 supported membranes - Santos, L. R B [UNESP]; Larbot, A.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Trans Tech Publications, 1997)
SnO2 supported membranes have been prepared by sol-casting on alumina tubular substrate, using aqueous colloidal suspensions prepared by sol-gel route. The viscoelastic behaviour during sol ageing was analyzed by dinamic rheologial measurements. The complex viscosity and the storage and loss moduli have been followed during the sol-gel transition and the results have been correlated with the linear aggregates growth and the scalar percolation models. The scanning electron microscopy has evidenced that the homogeneity and thickness of the membrane depend on the sol ageing time. Crack-free and homogeneous membranes have been obtained for coated layers of 0.5μm thickness. © 1997 Trans Tech Publications.
Keywords: SnO2 and Viscoelastic characteristics; Sol-gel; Aging of materials; Alumina; Casting; Colloids; Membranes; Rheology; Scanning electron microscopy; Sol-gels; Solutions; Suspensions (fluids); Viscoelasticity; Colloidal suspensions; Sol casting; Tin compounds